Preface - Gutkowski, W.; Wilmański, K. (Archives of Mechanics, 2006)
This double issue of Archives of Mechanics contains papers presented at International Conference on Continuous and Discrete Modelling in Mechanics, CDMM2005, in Memory of Professor Henryk Zorski which has taken place in the Institute of Fundamental Technological Research, Warsaw, September 5-9, 2005.